Examining the Impact of Repetition on the Eloquence of Bustan - بتول واعظ; رقیه کاردل ایلواری (مطالعات زبانی و بلاغی)
This study is aimed at discussing the various types of rhetorical and semantic repetition in didactic poetry based on Bustan. To this end, it has primarily investigated repetition from the perspective of rhetoricians followed by the dialectic bond of language and mind in didactic poetry. In the third section, rhetorical repetition in Bustan has been scrutinized. At the end, a novel type of repetition in the area of semantics in Saadiâs discourse is introduced which reveals that this type of repetition is found in the area of semantics with the purpose of transferring information, meaning, and thoughts through linguistic functions than creating music and demonstrating aesthetic appeal in discourse. Hence, this kind of repetition enjoys more linguistic application besides inducing aesthetic influences in the text which is studied in the area of semantics.